Storage stability and disinfection performance on Escherichia coli of electrolyzed seawater - Damalerio, Regina G. (Animo Repository, 2019)
© 2019 by the authors. The study investigated the effect of storage conditions on the stability of electrolyzed seawater (ESW)'s physicochemical properties (pH, oxidation-reduction potential (ORP), and free chlorine (FC) concentration), and bactericidal efficiency on the fecal coliform Escherichia coli for 30 days. Preliminary experiments were conducted to determine the optimal current and electrolysis time. Two batches of 2750 mL filtered seawater were electrolyzed using 50mm × 192mmplatinum-titanium mesh electrodes at a current of 1.5 A for 20 min. One hundred milliliters of electrolyzed solution was transferred into each amber glass and high-density polyethylene (HDPE) bottles. The bottles were stored in a dark area at ambient temperature. The results showed an increase in pH and a decrease in ORP and FC concentration through time. Hypochlorous acid remained as the dominant component since the pH levels of the solutions remained below 7.5. FC decay was investigated using Chick's Law. It was determined that the decay in HDPE bottles (k = -0.066 day-1) was faster compared to amber glass bottles (k = -0.046 day-1). Nonetheless, HDPE bottles could still be used as an alternative container for 30 days only due to observed instability beyond 30 days. ESW remained effective since no surviving population of E. coli was observed throughout the experimentation.